Assessing the dynamics of agricultural and price trends of geographical indication (GI) tagged Guntur Sannam chilli in Andhra Pradesh, India - SUDEEPTHI, K; VIDHYAVATHI, A; PRAHADEESWARAN, M; PARASURAMAN, BALAJI; VASANTHI, R; RANI, S PADMA; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2025)
Present study examines Guntur Sannam chilli, a crucial agricultural product in Andhra Pradesh, revealing notable increases in cultivation area and production based on 30 years of data (1993–94 to 2022–23) attributed to technological advancements and better land management, after GI registration. However, the growth in productivity was slower, potentially due to various limitations. The analysis employed ARCH-GARCH and VAR models to explore price volatility, underscoring the significance of historical price trends, showing hike in prices of Guntur Sannam chilli, after attaining GI tag; for effective risk management. Despite observed fluctuations, the overall market conditions appear relatively stable. Policy recommendations emphasize targeted interventions aimed at enhancing productivity, addressing existing constraints, and stabilizing prices, thereby laying a solid foundation for informed policymaking and future research in this domain.